Sachunterricht begründet planen. Das Prozessmodell Generativer Unterrichtsplanung Sachunterricht (GUS) und seine Grundlagen.

Roadmap on quantum light spectroscopy - Mukamel, Shaul; Freyberger, Matthias; Schleich, Wolfgang; Bellini, Marco; Zavatta, Alessandro; Leuchs, Gerd; Silberhorn, Christine; Boyd, Robert W; Sánchez-Soto, Luis Lorenzo; Stefanov, André; Barbieri, Marco; Paterova, Anna; et al. (Journal of Physics B: Atomic, Molecular and Optical Physics)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics

Single-photon sources: Approaching the ideal through multiplexing - Meyer-Scott, Evan; Silberhorn, Christine; Migdall, Alan (Review of Scientific Instruments)
Keywords: Instrumentation

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian R.; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of −1.648 ± 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source’s suitability for scalable hybrid quantum network applications with pulsed quantum light.
Keywords: Atomic and Molecular Physics; and Optics

Spatially single mode photon pair source at 800 nm in periodically poled Rubidium exchanged KTP waveguides - Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine (Optics Express)

Properties of bright squeezed vacuum at increasing brightness - Sharapova, Polina R.; Frascella, G.; Riabinin, M.; Pérez, A. M.; Tikhonova, O. V.; Lemieux, S.; Boyd, R. W.; Leuchs, G.; Chekhova, M. V. (Physical Review Research)
Keywords: General Engineering

Spatial entanglement and state engineering via four-photon Hong–Ou–Mandel interference - Ferreri, A; Ansari, V; Brecht, Benjamin; Silberhorn, Christine; Sharapova, Polina R. (Quantum Science and Technology)
Abstract The phenomenon of entanglement is the basis of quantum information and quantum communication processes. Entangled systems with a large number of photons are of great interest at present because they provide a platform for streaming technologies based on photonics. In this paper we present a device which operates with four-photons and based on the Hong–Ou–Mandel interference. The presented device allows to maximize the degree of spatial entanglement and generate the highly entangled four-dimensional Bell states. Furthermore, the use of the interferometer in different regimes leads to fast interference fringes in the coincidence probability with period of oscillations twice smaller than the pump wavelength. We have a good agreement between theoretical simulations and experimental results.
Keywords: Electrical and Electronic Engineering; Physics and Astronomy (miscellaneous); Materials Science (miscellaneous); Atomic and Molecular Physics; and Optics

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Vibrational Raman spectroscopy on adsorbate-induced low-dimensional surface structures - Speiser, Eugen; Esser, Norbert; Halbig, Benedikt; Geurts, Jean; Schmidt, Wolf Gero; Sanna, Simone (Surface Science Reports)

Detector-Agnostic Phase-Space Distributions - Sperling, Jan; Phillips, D. S.; Bulmer, J. F. F; Thekkadath, G. S.; Eckstein, A.; Wolterink, T. A. W.; Lugani, J.; Nam, S. W.; Lita, A.; Gerrits, T.; Vogel, W.; Agarwal, G. S.; et al. (Physical Review Letters)

Quantum photonics with active feedback loops - Engelkemeier, M.; Lorz, L.; De, Syamsundar; Brecht, Benjamin; Dhand, I.; Plenio, M. B.; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Local Versus Global Two-Photon Interference in Quantum Networks - Nitsche, Thomas; De, Syamsundar; Barkhofen, Sonja; Meyer-Scott, Evan; Tiedau, Johannes; Sperling, Jan; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Molecular doping in few-molecule polymer-dopant complexes shows reduced Coulomb binding - Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Coulomb binding energy is reduced when a few-molecule integer charge transfer complex (ICTC) is formed.
Keywords: Materials Chemistry; General Chemistry

Efficient Bosonic Condensation of Exciton Polaritons in an H-Aggregate Organic Single-Crystal Microcavity. - Ren, J; Liao, Q; Huang, H; Li, Y; Gao, T; Ma, Xuekai; Schumacher, Stefan; Yao, J; Bai, S; Fu, H (Nano Letters)

Formation dynamics of exciton-polariton vortices created by nonresonant annular pumping - Berger, Bernd; Schmidt, Daniel; Ma, Xuekai; Schumacher, Stefan; Schneider, Christian; Höfling, Sven; Assmann, Marc (Physical Review B)

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Circular polarization reversal of half-vortex cores in polariton condensates - Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Spiraling vortices in exciton-polariton condensates - Ma, Xuekai; Kartashov, Yaroslav V.; Gao, Tingge; Torner, Lluis; Schumacher, Stefan (Physical Review B)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Externally controlled Lotka-Volterra dynamics in a linearly polarized polariton fluid - Pukrop, Matthias; Schumacher, Stefan (Physical Review E)

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Toward Efficient Toxic-Gas Detectors: Exploring Molecular Interactions of Sarin and Dimethyl Methylphosphonate with Metal-Centered Phthalocyanine Structures - Aldahhak, Hazem; Powroźnik, Paulina; Pander, Piotr; Jakubik, Wiesław; Dias, Fernando B.; Schmidt, Wolf Gero; Gerstmann, Uwe; Krzywiecki, Maciej (The Journal of Physical Chemistry C)

Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Tetracene Ultrathin Film Growth on Hydrogen-Passivated Silicon - Niederhausen, Jens; MacQueen, Rowan W.; Lips, Klaus; Aldahhak, Hazem; Schmidt, Wolf Gero; Gerstmann, Uwe (Langmuir)

Photochemical Ring Opening of Oxirane Modeled by Constrained Density Functional Theory - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (ACS Omega)

Carrier-wave population transfer in semiconductors - Zuo, R; Song, X; Meier, Torsten; Yang, W (Journal of Physics: Conference Series)

Probing nonclassicality with matrices of phase-space distributions - Bohmann, Martin; Agudelo, Elizabeth; Sperling, Jan (Quantum)
We devise a method to certify nonclassical features via correlations of phase-space distributions by unifying the notions of quasiprobabilities and matrices of correlation functions. Our approach complements and extends recent results that were based on Chebyshev's integral inequality \cite{BA19}. The method developed here correlates arbitrary phase-space functions at arbitrary points in phase space, including multimode scenarios and higher-order correlations. Furthermore, our approach provides necessary and sufficient nonclassicality criteria, applies to phase-space functions beyond s-parametrized ones, and is accessible in experiments. To demonstrate the power of our technique, the quantum characteristics of discrete- and continuous-variable, single- and multimode, as well as pure and mixed states are certified only employing second-order correlations and Husimi functions, which always resemble a classical probability distribution. Moreover, nonlinear generalizations of our approach are studied. Therefore, a versatile and broadly applicable framework is devised to uncover quantum properties in terms of matrices of phase-space distributions.

Classical evolution in quantum systems - Sperling, Jan; Walmsley, I A (Physica Scripta)

Transfer function replacement of phenomenological single-mode equations in semiconductor microcavity modeling - Carcamo, M.; Schumacher, Stefan; Binder, R. (Applied Optics)
Semiconductor microcavities are frequently studied in the context of semiconductor lasers and in application-oriented fundamental research on topics such as linear and nonlinear polariton systems, polariton lasers, polariton pattern formation, and polaritonic Bose–Einstein condensates. A commonly used approach to describe theoretical properties includes a phenomenological single-mode equation that complements the equation for the nonlinear optical response (interband polarization) of the semiconductor. Here, we show how to replace the single-mode equation by a fully predictive transfer function method that, in contrast to the single-mode equation, accounts for propagation, retardation, and pulse-filtering effects of the incident light field traversing the distributed Bragg reflector (DBR) mirrors, without substantially increasing the numerical complexity of the solution. As examples, we use cavities containing GaAs quantum wells and transition-metal dichalcogenides (TMDs).
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

Realization of all-optical vortex switching in exciton-polariton condensates - Meier, Torsten; Ma, Xuekai; Berger, Bernd; Aßmann, Marc; Driben, Rodislav; Schneider, Christian; Höfling, Sven; Schumacher, Stefan (Nature communications)
Vortices are topological objects representing the circular motion of a fluid. With their additional degree of freedom, the vorticity, they have been widely investigated in many physical systems and different materials for fundamental interest and for applications in data storage and information processing. Vortices have also been observed in non-equilibrium exciton-polariton condensates in planar semiconductor microcavities. There they appear spontaneously or can be created and pinned in space using ring-shaped optical excitation profiles. However, using the vortex state for information processing not only requires creation of a vortex but also efficient control over the vortex after its creation. Here we demonstrate a simple approach to control and switch a localized polariton vortex between opposite states. In our scheme, both the optical control of vorticity and its detection through the orbital angular momentum of the emitted light are implemented in a robust and practical manner.

k.p-based multiband simulations of non-degenerate two-photon absorption in bulk GaAs - Hannes, Wolf-Rüdiger; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIV)

Strongly nonresonant four-wave mixing in semiconductors - Hannes, W.-R.; Trautmann, Alexander; Stein, M.; Schäfer, F.; Koch, M.; Meier, Torsten (Physical Review B)

Enhanced high-order harmonic generation in semiconductors by excitation with multicolor pulses - Song, Xiaohong; Yang, Shidong; Zuo, Ruixin; Meier, Torsten; Yang, Weifeng (Physical Review A)

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Realization of all-optical vortex switching in exciton-polariton condensates - Ma, Xuekai; Berger, B; Aßmann, M; Driben, R; Meier, Torsten; Schneider, C; Höfling, S; Schumacher, Stefan (Nature Communications)

Physik in der Lehrerinnen- und Lehrerbildung. Auf dem Weg zu empirisch fundierten Curricula - Reinhold, Peter; Riese, Josef (Handbuch Lehrerinnen- und Lehrerbildung)

Die Messung der Fähigkeit zur Unterrichtsplanung im Fach Physik mit Hilfe eines standardisierten Performanztests - Schröder, Jan; Riese, Josef; Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Die Unterrichtsplanung stellt eine zentrale berufliche Anforderung an (Physik‑)Lehrkräfte dar. Bereits im Lehramtsstudium sollen grundlegende Fähigkeiten zur Unterrichtsplanung erworben und im Rahmen von schulpraktischen Phasen erprobt bzw. erweitert werden. Unklar ist jedoch, inwieweit das professionelle Wissen, das Lehramtsstudierende in ihren fachlichen, fachdidaktischen und erziehungswissenschaftlichen Studienteilen erwerben, tatsächlich bei der Planung von Fachunterricht genutzt wird. Ebenso gibt es nur punktuelle Erkenntnisse über die Entwicklung der Fähigkeit zur Unterrichtsplanung im Lehramtsstudium. Um diese Fragen zu klären, sind Messverfahren erforderlich, die die Fähigkeiten zur Unterrichtsplanung valide erfassen können und die gleichzeitig ökonomisch auswertbar sind, um Fallzahlen realisieren zu können, die auch kleine Effekte auflösen. Bisherige Ansätze, die reale Handlungsproben der Unterrichtsplanung (z. B. schriftliche Unterrichtsentwürfe) untersuchen, stehen vor der methodischen Herausforderung, dass die Generierung eines Fähigkeitsmaßes höchst anspruchsvoll ist, da reale Planungen individuell sehr unterschiedlich angelegt sind und vielen Randbedingungen unterliegen, die statistisch kaum kontrollierbar sind. In diesem Beitrag wird daher ein sogenannter Performanztest zur Erfassung der Fähigkeit zur Unterrichtsplanung vorgestellt und diskutiert. Ein Performanztest ist ein Verfahren, in dem in einem realitätsnahen Setting Handlungen unter standardisierten Rahmenbedingungen simuliert werden. Neben der theoriegeleiteten Entwicklung des Instruments und Vorstudien zur Sammlung von Validitätsargumenten werden auch erste Ergebnisse dargestellt, die aus Erhebungen vor und nach einem Praxissemester an vier Universitäten in drei Bundesländern resultieren ( N = 174 Unterrichtsplanungen). Dabei stellt sich das Testverfahren als ausreichend sensitiv heraus, um für N = 68 Testpersonen (ca. 20 % Dropout) erwartungstreu eine signifikante Zunahme des Testscores während des Praxissemesters, welches als Lerngelegenheit angenommen werden kann, zu messen.

Development of Prospective Physics Teachers’ Professional Knowledge and Skills during a One-Semester School Internship - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Schecker, Horst; Schröder, Jan (Student Learning in German Higher Education)

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Messung der Fähigkeit zur Unterrichtsplanung bei Lehramtsstudierenden - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Ursachen für Veränderungen des physikdidaktischen Wissens im Studium - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Basismodelle in Unterrichtsplanungen im Praxissemester Physik - Buschhütter, David; Mutschler, Tanja; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Entwicklung eines Fachpraktikums im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Wie entwickeln sich Wissen und Fähigkeiten im Physiklehramtsstudium? - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Nonlinear focal mapping of ferroelectric domain walls in LiNbO3: Analysis of the SHG microscopy contrast mechanism - Spychala, K. J.; Mackwitz, P.; Rüsing, Michael; Widhalm, A.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)

Characterisation of width-dependent diffusion dynamics in rubidium-exchanged KTP waveguides - Padberg, Laura; Santandrea, Matteo; Rüsing, Michael; Brockmeier, Julian; Mackwitz, Peter; Berth, Gerhard; Zrenner, Artur; Eigner, Christof; Silberhorn, Christine (Optics Express)

Erhebung der experimentellen Performanz (Physik-)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe)

Improving SPDC single-photon sources via extended heralding and feed-forward control - Massaro, Marcello; Meyer-Scott, Evan; Montaut, Nicola; Herrmann, Harald; Silberhorn, Christine (New Journal of Physics)

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Molecular beam epitaxy growth and temperature-dependent electrical characterization of carbon-doped GaAs on GaAs(1 1 1)B - Henksmeier, Tobias; Shvarkov, Stepan; Trapp, Alexander; Reuter, Dirk (Journal of Crystal Growth)

Nonlinear optics in all-dielectric nanoantennas and metasurfaces: a review - Sain, Basudeb; Meier, Cedrik; Zentgraf, Thomas (Advanced Photonics)
Free from phase-matching constraints, plasmonic metasurfaces have contributed significantly to the control of optical nonlinearity and enhancement of nonlinear generation efficiency by engineering subwavelength meta-atoms. However, high dissipative losses and inevitable thermal heating limit their applicability in nonlinear nanophotonics. All-dielectric metasurfaces, supporting both electric and magnetic Mie-type resonances in their nanostructures, have appeared as a promising alternative to nonlinear plasmonics. High-index dielectric nanostructures, allowing additional magnetic resonances, can induce magnetic nonlinear effects, which, along with electric nonlinearities, increase the nonlinear conversion efficiency. In addition, low dissipative losses and high damage thresholds provide an extra degree of freedom for operating at high pump intensities, resulting in a considerable enhancement of the nonlinear processes. We discuss the current state of the art in the intensely developing area of all-dielectric nonlinear nanostructures and metasurfaces, including the role of Mie modes, Fano resonances, and anapole moments for harmonic generation, wave mixing, and ultrafast optical switching. Furthermore, we review the recent progress in the nonlinear phase and wavefront control using all-dielectric metasurfaces. We discuss techniques to realize all-dielectric metasurfaces for multifunctional applications and generation of second-order nonlinear processes from complementary metal–oxide–semiconductor-compatible materials.

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim; Silberhorn, Christine (Optics Express)

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Reconfigurable metasurface hologram by utilizing addressable dynamic pixels - Li, Tianyou; Wei, Qunshuo; Reineke, Bernhard; Walter, Felicitas; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Optics Express)

Silicon metasurfaces for third harmonic geometric phase manipulation and multiplexed holography - Reineke, Bernhard; Sain, Basudeb; Zhao, Ruizhe; Carletti, Luca; Liu, Bingyi; Huang, Lingling; de Angelis, Costantino; Zentgraf, Thomas (Nano Letters)

Metasurface interferometry toward quantum sensors - Georgi, Philip; Massaro, Marcello; Luo, Kai Hong; Sain, Basudeb; Montaut, Nicola; Herrmann, Harald; Weiss, Thomas; Li, Guixin; Silberhorn, Christine; Zentgraf, Thomas (Light: Science & Applications)

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)

Scalability of parametric down-conversion for generating higher-order Fock states - Tiedau, Johannes; Bartley, Tim; Harder, Georg; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review A)

Four‐Wave Mixing Holographic Multiplexing Based on Nonlinear Metasurfaces - Lin, Zemeng; Huang, Lingling; Xu, Zhen Tao; Li, Xiaowei; Zentgraf, Thomas; Wang, Yongtian (Advanced Optical Materials)

Dynamic control of mode modulation and spatial multiplexing using hybrid metasurfaces - Lin, Zemeng; Huang, Lingling; Zhao, Ruizhe; Wei, Qunshuo; Zentgraf, Thomas; Wang, Yongtian; Li, Xiaowei (Optics Express)

Miniaturized Metalens Based Optical Tweezers on Liquid Crystal Droplets for Lab-on-a-Chip Optical Motors - Suwannasopon, Satayu; Meyer, Fabian; Schlickriede, Christian; Chaisakul, Papichaya; T-Thienprasert, Jiraroj; Limtrakul, Jumras; Zentgraf, Thomas; Chattham, Nattaporn (Crystals)
Surfaces covered with layers of ultrathin nanoantenna structures—so called metasurfaces have recently been proven capable of completely controlling phase of light. Metalenses have emerged from the advance in the development of metasurfaces providing a new basis for recasting traditional lenses into thin, planar optical components capable of focusing light. The lens made of arrays of plasmonic gold nanorods were fabricated on a glass substrate by using electron beam lithography. A 1064 nm laser was used to create a high intensity circularly polarized light focal spot through metalens of focal length 800 µm, N.A. = 0.6 fabricated based on Pancharatnam-Berry phase principle. We demonstrated that optical rotation of birefringent nematic liquid crystal droplets trapped in the laser beam was possible through this metalens. The rotation of birefringent droplets convinced that the optical trap possesses strong enough angular momentum of light from radiation of each nanostructure acting like a local half waveplate and introducing an orientation-dependent phase to light. Here, we show the success in creating a miniaturized and robust metalens based optical tweezers system capable of rotating liquid crystals droplets to imitate an optical motor for future lab-on-a-chip applications.

Strong Nonlinear Optical Activity Induced by Lattice Surface Modes on Plasmonic Metasurface - Chen, Shumei; Reineke, Bernhard; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan

Reflexionskompetenz trainieren: Unterrichtsvideographie als Werkzeug zur fachdidaktischen Begleitung im Praxissemester - Vogelsang, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Den Einsatz digitaler Medien im naturwissenschaftlichen Unterricht lehren - Untersuchung der Lehrinitiative Didaktik:digital im Spannungsfeld von standortübergreifender Wirkungsanalyse und standortspezifischer Evaluation - Vogelsang, Christoph (Hochschuldidaktik erforscht Qualität - Profilbildung und Wertefragen in der Hochschulentwicklung III)

Integrated transition edge sensors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Gerrits, Thomas; Lita, Adriana; Krapick, Stephan; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Mirin, Richard; Nam, Sae Woo; Silberhorn, Christine; Bartley, Tim (APL Photonics)

Durchgängige Sprachbildung und Inklusion in der sachunterrichtsdidaktischen Lehrer*innenbildung. Eine interdisziplinäre Evaluationsstudie mit Sachunterrichtsstudierenden - Blumberg, Eva; Niederhaus, Constanze; Albers, Timm; Havkic, Amra (Inklusion im Sachunterricht)

Herstellung von Wellenleitern aus Materialien der KTP-Familie - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Kooperatives Arbeiten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven Unterricht in der Grundschule. Posterpräsentation auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Effects of Interprofessional Collaboration in Inclusive Education of Pre-Service Primary School Teachers and Special Education Teachers on their Self-Concepts. Poster Presentation. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Kooperativ Lernumgebungen für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule gestalten – ein Forschungs- und Entwicklungsprojekt zur Förderung von Grund- und Förderschullehrkräften (KLinG). Posterpräsentation auf der 28. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts e. V. (GDSU) - Mester, Theresa; Blumberg, Eva; Kirsch, Alexander; Hellmich, Frank; Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Schwab, Susanne

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Curved Polar Dibenzocoronene Esters and Imides versus Their Planar Centrosymmetric Homologs: Photophysical and Optoelectronic Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Externally Controlled Lotka-Volterra Dynamics in a Linearly Polarized Polariton Fluid - Pukrop, Matthias; Schumacher, Stefan (arXiv:1903.12534)
Spontaneous formation of transverse patterns is ubiquitous in nonlinear dynamical systems of all kinds. An aspect of particular interest is the active control of such patterns. In nonlinear optical systems this can be used for all-optical switching with transistor-like performance, for example realized with polaritons in a planar quantum-well semiconductor microcavity. Here we focus on a specific configuration which takes advantage of the intricate polarization dependencies in the interacting optically driven polariton system. Besides detailed numerical simulations of the coupled light-field exciton dynamics, in the present paper we focus on the derivation of a simplified population competition model giving detailed insight into the underlying mechanisms from a nonlinear dynamical systems perspective. We show that such a model takes the form of a generalized Lotka-Volterra system for two competing populations explicitly including a source term that enables external control. We present a comprehensive analysis both of the existence and stability of stationary states in the parameter space spanned by spatial anisotropy and external control strength. We also construct phase boundaries in non-trivial regions and characterize emerging bifurcations. The population competition model reproduces all key features of the switching observed in full numerical simulations of the rather complex semiconductor system and at the same time is simple enough for a fully analytical understanding of the system dynamics.

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Pre-service Primary School Teachers’ Preparation for Team-Teaching in Inclusive Schools. Poster Presentation. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Hoya, Fabian Karl; Löper, Marwin Felix; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Molecular Doping of PCPDT-BT Copolymers: Comparison of Molecular Complexes with and Without Integer Charge Transfer - Dong, Chuan-Ding; Schumacher, Stefan
Molecular doping in conjugated polymers is a crucial process for their application in organic photovoltaics and optoelectronics. In the present work we theoretically investigate p-type molecu- lar doping in a series of (poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b”]dithiophene)-alt- 4,7-(2,1,3-benzothiadiazole)] (PCPDT-BT) conjugated oligomers with different lengths and three widely-used dopants with different electron affinities, namely F4TCNQ, F6TCNNQ, and CN6-CP. We study in detail the molecular geometry of possible oligomer-dopant complexes and its influence on the doping mechanisms and electronic system properties. We find that the mechanisms of dop- ing and charge transfer observed sensitively depend on the specific geometry of the oligomer-dopant complexes. For a given complex different geometries may exist, some of which show transfer of an entire electron from the oligomer chain onto the dopant molecule resulting in an integer-charge transfer complex, leaving the system in a ground state with broken spin symmetry. In other ge- ometries merely hybridization of oligomer and dopant frontier orbitals occurs with partial charge transfer but spin-symmetric ground state. Considering the resulting electronic density of states both cases may well contribute to an increased electrical conductivity of corresponding film samples while the underlying physical mechanisms are entirely different.

Wie können Studierende des Lehramts an Grund- und Förderschulen auf das kooperative Arbeiten in der inklusiven Grundschule vorbereitet werden? Posterpräsentation auf der 7. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Entwicklung kooperativen Arbeitens bei Lehramtsstudierenden für den naturwissenschaftlichen Sachunterricht in der inklusiven Grundschule. Posterpräsentation auf dem 8. Paderborner Grundschultag - Löper, Marwin Felix; Görel, Gamze; Hoya, Fabian Karl; Kirsch, Alexander; Mester, Theresa; Schulze, Jan Roland; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)